Cooperative Catalysis: Combining an Achiral Metal Catalyst with a Chiral Brønsted Acid Enables Highly Enantioselective Hydrogenation of Imines. Issue 42 (9th September 2013) - Tang, Weijun; Johnston, Steven; Li, Chaoqun; Iggo, Jonathan A.; Bacsa, John; Xiao, Jianliang
Abstract Asymmetric hydrogenation of imines leads directly to chiral amines, one of the most important structural units in chemical products, from pharmaceuticals to materials. However, highly effective catalysts are rare. This article reveals that combining an achiral pentamethylcyclopentadienyl (Cp*)–iridium complex with a chiral phosphoric acid affords a catalyst that allows for highly enantioselective hydrogenation of imines derived from aryl ketones, as well as those derived from aliphatic ones, with ee values varying from 81 to 98 %. A range of achiral iridium complexes containing diamine ligands were examined, for which the ligands were shown to have a profound effect on the reaction rate, enantioselectivity and catalyst deactivation. The chiral phosphoric acid is no less important, inducing enantioselection in the hydrogenation. The induction occurs, however, at the expense of the reaction rate.